2002
DOI: 10.1080/09537100120104890
|View full text |Cite
|
Sign up to set email alerts
|

Towards a definition of aspirin resistance: a typological approach

Abstract: 'Aspirin resistance' is a poorly defined term to describe the inability of aspirin to protect individuals from thrombotic complications and there are conflicting reports on incidence rates and clinical relevance of this phenomenon. Using collagen (1 microg/ml)-induced platelet aggregation and thromboxane formation (measured as thromboxane B(2)) in citrated platelet-rich plasma, this study demonstrates that aspirin resistance can be classified into three distinct types. In aspirin responders, both, collagen-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 17 publications
3
109
0
4
Order By: Relevance
“…18 Aspirin resistance involves, besides thromboxane formation, an impaired inhibition of platelet aggregation and an increased expression of P-selectin, a marker of ␣-granule secretion associated with the progression of atherosclerosis. 19 We have previously proposed to classify aspirin resistance into three major categories, 20 of which one (type 1) includes the inhibition of platelet thromboxane formation in vitro but not in vivo (pharmacokinetic type). Type 2 is characterized by the inability of aspirin to inhibit platelet thromboxane formation in vivo and in vitro (pharmacodynamic type).…”
Section: Discussionmentioning
confidence: 99%
“…18 Aspirin resistance involves, besides thromboxane formation, an impaired inhibition of platelet aggregation and an increased expression of P-selectin, a marker of ␣-granule secretion associated with the progression of atherosclerosis. 19 We have previously proposed to classify aspirin resistance into three major categories, 20 of which one (type 1) includes the inhibition of platelet thromboxane formation in vitro but not in vivo (pharmacokinetic type). Type 2 is characterized by the inability of aspirin to inhibit platelet thromboxane formation in vivo and in vitro (pharmacodynamic type).…”
Section: Discussionmentioning
confidence: 99%
“…However, the adverse effects of oral ASA tablets such as gastrointestinal disorders and bleeding often led to treatment discontinuation. Furthermore, many studies found that some patients would get aspirin resistance (AR) or aspirin failure (AF) [5]. All of these limited the application of ASA.…”
Section: Introductionmentioning
confidence: 99%
“…Some study the prevalence of aspirin resistance and how to achieve defining its presence, [6][7][8] some study the mechanisms for aspirin resistance, [9][10][11][12] and yet others examine the impact or clin-ical significance of aspirin resistance on the presence or development of cardiovascular disease [13][14][15][16][17][18][19][20][21] (Table I). There is no consensus on the ideal technique for the assessment of the presence of aspirin resistance and therefore no agreement about a standardized definition.…”
Section: Discussionmentioning
confidence: 99%